The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
AIAA SPACE 2008 Conference &Amp; Exposition 2008
DOI: 10.2514/6.2008-7823
|View full text |Cite
|
Sign up to set email alerts
|

Architecture Modeling of In-Situ Oxygen Production and its Impacts on Lunar Campaigns

Abstract: In-situ lunar oxygen production has the potential to reduce the cargo mass launched from Earth necessary to sustain a lunar base. As research and development in lunar oxygen production continue, modeling tools are being used to help characterize the many possible system architectures and guide decisions for future plant designs. Using the previously built NASA In-Situ Resource Utilization (ISRU) System Model, an optimization tool was developed to facilitate exploration of the design space of the different syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
(9 reference statements)
0
13
0
Order By: Relevance
“…The baseline problem assumes a linear ISRU resource production rate of 10 kg per year per unit plant mass. A previous study showed that ISRU plants follow economies of scale, meaning that larger plants would be less costly to achieve the same total production rate [8,10]. With that, a production rate of 10 kg/year/kg might be too optimistic especially for smaller plants, even with technological advancement in the future.…”
Section: G Isru Productivitymentioning
confidence: 99%
See 2 more Smart Citations
“…The baseline problem assumes a linear ISRU resource production rate of 10 kg per year per unit plant mass. A previous study showed that ISRU plants follow economies of scale, meaning that larger plants would be less costly to achieve the same total production rate [8,10]. With that, a production rate of 10 kg/year/kg might be too optimistic especially for smaller plants, even with technological advancement in the future.…”
Section: G Isru Productivitymentioning
confidence: 99%
“…In this study it is assumed that the ISRU system is automated or teleoperated with robots and that both the maintenance requirement and the resource productivity are linearly scalable with respect to the size of the system. While a previous study showed that ISRU plants actually follow economies of scale [8,10], this study takes advantage of LP formulation by assuming linear scalability. Let α and β be the proportional constants for maintenance requirement (ISRU spares) and resource productivity, respectively.…”
Section: Isru Resource Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen is a consumable resource used to supply crew air and oxidizer in rocket propellant that can be extracted from the lunar regolith. Systems to perform lunar oxygen extraction are being studied and built by NASA, including the development of a system modeling tool that captures the many architecture alternatives in the system selection and design 2,3 . Several chemical processes can be used to produce oxygen from the metal oxides and glasses present in lunar soil, but because there is no historical data to draw from in the design of these systems, a detailed set of engineering models has been constructed to help assess the systemlevel trades of some of these processes.…”
Section: Introductionmentioning
confidence: 99%
“…Given the economy of scale analysis previously perform on the ISRU OPS using the ISRU modeling tool reported in Ref. 12, it would be more efficient to have fewer OPS with higher production rates. Hence, the smarter lower risk approach would be to have a series of OPS that progressively increase in capability as the system mature.…”
Section: A Water Production and Accumulationmentioning
confidence: 99%